‘An Unusual Case Of Dyadic Death’- A Case Report (Indian Internet Journal of Forensic Medicine and Toxicology, 2025)
A dyadic death is a rare but tragic form of Premeditated violence that involves the  death of two people at the same time (homicide followed by a suicide), or suicide  pact, where a person kills another person and then commits suicide. Dyadic deaths  make up a small proportion of homicide overall, commonly in low socio-economic,  less educated or illiterate families. This is a case report on one such incident where  the perpetrator killed the victim with whom he had a long-standing property dispute  and also his own mother who tried to stop him from doing the act, following which  he killed himself by shooting himself with a .315 pistol.
Keywords: Dyadic death; Head injury; Firearm injury; Perforation Peritonitis